Faktor-Faktor yang Berhubungan dengan Pernikahan Usia Dini di Kabupaten Purworejo Jawa Tengah - Rafidah Ova Emilia, Budi Wahyuni (Fakultas Kedokteran Universitas Gadjah Mada, 2009)
Background: Early marriage is common in developing countries including Indonesia. Factors related to early marriage are, among others; education, economic, and social aspects. The impacts of early marriage are dropout and teenage pregnancy which causes rejection to pregnancy. In District of Purworejo marriage below 20 years of age is still as much as 20.6% (Community Health and Nutrition Research Laboratory 2005).Objective: The study aimed to identify factors related to early marriage.Method: This was an observational study with cross sectional design using both qualitative and quantitative approaches. Data were obtained through questionnaires and interview guide. Samples of the study were 90 married women, who were systematically chosen, respondents of longitudinal surveillance of Community Health and Nutrition Research Laboratory, 90 parents of the respondent, 1 religious leader, 2 community leaders and 1 staff of office of Religious Affairs. Hypothetical test used chi square with p<0.05, CI 95%. Multivariable analysis used logistic regression.Results: Low perception about marriage showed the most related to the decision for early marriage. Other factors related to early marriage were low level of education (RP=2.90, CI 95%=1.30–6.49, p=0.000), low familyeconomic status (RP=1.75, CI 95%=1.05 – 2.91 p=0.017). Unemployed parents (RP=1.48, CI95%=0.88-2.49 p=0.23) and parents’ low perception about marriage (RP=1.5, CI95%=0.96-2.37 p=0.05) were not strongly related with early marriage.Conclusion: Factors related to early marriage were perception of respondents about marriage, education of respondents, family economic status, and unemployed parents.Keywords: early marriage, perception about marriage, family economic status, education